2020
DOI: 10.1038/s41598-019-57358-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genetic polymorphisms modulating nausea and vomiting in two series of opioid-treated cancer patients

Abstract: Nausea and vomiting are often associated with opioid analgesia in cancer patients; however, only a subset of patients develop such side effects. Here, we tested the hypothesis that the occurrence of nausea and vomiting is modulated by the genetic background of the patients. Whole exome sequencing of DNA pools from patients with either low (n = 937) or high (n = 557) nausea and vomiting intensity, recruited in the European Pharmacogenetic Opioid Study, revealed a preliminary association of 53 polymorphisms. PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Genotyping of 45 ONVs demonstrated the association of SNVs of AIM1L, CLCC1, MUC16, PDE3A, POM121L2 and ZNF165 genes with the risk of opioidassociated constipation [20]. In Italian cancer patients, the presence of an association of two SNVs in the ZNF568 and PDE3A genes with the risk of opioid-associated constipation was also shown [20]. The diversity of the studied genes, as well as ethnic and territorial characteristics, could explain the inconsistency of our results.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Genotyping of 45 ONVs demonstrated the association of SNVs of AIM1L, CLCC1, MUC16, PDE3A, POM121L2 and ZNF165 genes with the risk of opioidassociated constipation [20]. In Italian cancer patients, the presence of an association of two SNVs in the ZNF568 and PDE3A genes with the risk of opioid-associated constipation was also shown [20]. The diversity of the studied genes, as well as ethnic and territorial characteristics, could explain the inconsistency of our results.…”
Section: Discussionmentioning
confidence: 56%
“…The limited sample size of patients with pancreatic cancer in our study may have also provided the specificity of the collected data only for this category of patients. Genotyping of 45 ONVs demonstrated the association of SNVs of AIM1L, CLCC1, MUC16, PDE3A, POM121L2 and ZNF165 genes with the risk of opioidassociated constipation [20]. In Italian cancer patients, the presence of an association of two SNVs in the ZNF568 and PDE3A genes with the risk of opioid-associated constipation was also shown [20].…”
Section: Discussionmentioning
confidence: 98%
“…Whole exome sequencing of DNA pools revealed that six single nucleotide polymorphisms in some genes including AIM1L were associated with nausea and vomiting in opioid-treated cancer patients [47]. Unfortunately, impact of AIM1L on tumorigenesis is rarely investigated.…”
Section: Discussionmentioning
confidence: 99%
“…A pharmacogenomics study indicated that the risk of nausea and vomiting in opioid-treated cancer patients has a genetic component. Whole exome sequencing of DNA pools revealed that six single nucleotide polymorphisms in some genes including AIM1L were associated with nausea and vomiting in opioid-treated cancer patients [ 47 ]. Unfortunately, impact of AIM1L on tumorigenesis is rarely investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In the European Opioid Genetics Study (EPS), Colombo et al [46] calculated and analyzed the nausea and vomiting score (NVS) after opioid analgesia in 1494 cancer patients and found a strong correlation between PDE3A rs12305038 and NVS. Thus, mutations in these taste-altering enzymes may also modulate the response to nausea and vomiting.…”
Section: Pde3amentioning
confidence: 99%